2020
DOI: 10.1007/s10447-020-09411-z
|View full text |Cite
|
Sign up to set email alerts
|

Examining Secondary Trauma as a Result of Clients’ Reports of Discrimination

Abstract: In the current study, we examined the extent to which 86 American clinicians heard reports of discrimination from their clients of color. Findings indicated that 96.5% of clinicians heard at least one report of discrimination from clients of color at least occasionally in counseling. The acts of discrimination most frequently reported by clients of color were: a) being made to feel like outsiders, b) treated unfairly by coworkers and classmates, and c) treated unfairly by teachers and principals. Additionally,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(20 citation statements)
references
References 29 publications
1
19
0
Order By: Relevance
“…Exhaustion and depression are two symptoms that might indicate burnout in mental health professionals (Merriman, 2015;Wood et al, 2017). Similar to other studies, burnout and STS displayed significant positive correlation (Giordano et al, 2020). Therefore, STS may contribute to burnout for Black mental health therapists, and burnout may exacerbate STS (Cieslak et al, 2014).…”
Section: Discussionsupporting
confidence: 73%
See 3 more Smart Citations
“…Exhaustion and depression are two symptoms that might indicate burnout in mental health professionals (Merriman, 2015;Wood et al, 2017). Similar to other studies, burnout and STS displayed significant positive correlation (Giordano et al, 2020). Therefore, STS may contribute to burnout for Black mental health therapists, and burnout may exacerbate STS (Cieslak et al, 2014).…”
Section: Discussionsupporting
confidence: 73%
“…Kirkinis et al (2018) reported that higher levels of race-related stress or discrimination were also associated with higher levels of trauma symptoms for African Americans. Giordano et al (2020) found, for a sample that consisted primarily of White mental health therapists, that client reports of discrimination were significantly correlated with STS for the therapists in their study. Black mental health therapists may be at risk for STS because of their work with Black clients who experience racism.…”
Section: Burnout Secondary Trauma and Mental Health Therapistsmentioning
confidence: 78%
See 2 more Smart Citations
“…However, existing studies present competing evidence on how working condition affects human service professionals' mental health. Several early studies suggest that working in human services deteriorates workers' mental health (Adams et al, 2008;Conrad & Kellar-Guenther, 2006;Craig & Sprang, 2010;Giordano et al, 2021). This is because the hours devoted to listening to clients' distress can be stressful for workers (Fligey, 1995).…”
Section: Introductionmentioning
confidence: 99%